The Effectf of Room Facilities on Guest Satisfaction at Ima Kupang Hotel - Tamonob, Angel; Lasibey, Ariance Ana; Welly, Fahri; Ringa, Maria (Journal of Practical Management Studies, 2024)
The problems in this study are as follows: How does the influence of room facilities on guest satisfaction at the IMA Kupang Hotel? Based on the formulation of the problem, the goal is to determine the effect of room facilities on guest satisfaction at Hotel IMA Kupang. This study uses Room Facilities as the independent variable and Guest Satisfaction as the dependent variable. This research was conducted at the IMA Kupang Hotel, the number of samples was 90 respondents using the simple random sampling technique. Field data collection using a questionnaire. Based on the results of the descriptive analysis, the achievement variable for Room Facilities (X) is 1,919 with high criteria, the achievement variable for Guest Satisfaction (Y) is 2,208 with high criteria. The calculated t value for variable X is 12,258 while the t table value is 1,662, because the t calculated value is greater than t table (12,258 > 1,662) and the sig table shows a value of 0.000 which is smaller than the error rate of 0.1 (0.00 <0,1) then H0 is rejected and Ha is accepted. Thus the results of the Hypothesis test are Room Facilities have a significant effect on guest satisfaction at Hotel IMA Kupang. The results of the correlation analysis, obtained the value of R = 0.631ᵃ Square or the coefficient of determination which shows the influence of room facilities and guest satisfaction variables is relatively strong. The coefficient of determination is 0.631 or 63% and the remaining 37% is explained by other factors not examined.